2017
DOI: 10.1002/mnfr.201600506
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid drives the differentiation of mesoderm‐derived embryonic stem cells. Involvement of p38 MAPK/CREB and SVCT2 transporter

Abstract: The study demonstrated that AA drives mesoderm-derived stem cell differentiation toward myogenesis and osteogenesis and also inhibits adipogenesis. Further experiments found that AA competes with retinoic acid (RA) to drive cell differentiation in a dose-dependent manner: AA inhibited neurogenic differentiation and stimulated myogenesis whereas RA did the reverse. The AA-dependent differentiation of embryonic stem cells was shown to involve a p38 MAPK/CREB pathway, probably stimulated by cAMP via adenylate cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…is concentration may induce a switch in hGF activity from cell viability and migration to ECM production. Our findings revealed that the effects of vitamin C were dose-dependent corresponding with the findings of Rahman et al [24]. e higher concentrations of vitamin C, resulting in reduced cell viability, are unresolved.…”
Section: Discussionsupporting
confidence: 81%
“…is concentration may induce a switch in hGF activity from cell viability and migration to ECM production. Our findings revealed that the effects of vitamin C were dose-dependent corresponding with the findings of Rahman et al [24]. e higher concentrations of vitamin C, resulting in reduced cell viability, are unresolved.…”
Section: Discussionsupporting
confidence: 81%
“…Differentiation and regenerative capabilities of BMSCs can be enhanced by manipulating the cellular micro-environment. One goal of regenerative medicine is to optimize the regenerative potential of BMSCs through nutritional supplementation [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Vitamin C is one of the most important players in cell proliferation, differentiation, extracellular matrix (ECM) synthesis and cytoskeletal development [ 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Micronutrients, including vitamin C, are important factors in musculoskeletal development and BMSC biology [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. For example, vitamin C is a key player in collagen synthesis, cell proliferation, and BMSC differentiation [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of AA in the context of body weight could be at least partially related to stem cell differentiation towards myogeneis and osteogenesis, inhibiting adipogenesis. Since aging is associated with sarcopenia and defects in body weight, the current observations suggest that AA-mediated stem cell effects could play a role in the aging process [ 36 , 37 ].…”
Section: Ascorbic Acid and The Aging Process: In Vitro Modelsmentioning
confidence: 99%